The comparative economic status of CDEP and non-CDEP community residents in the Northern Territory in 1991 - Altman, Jon C., 1954-; Hunter, Boyd.; Australian National University. Centre for Aboriginal Economic Policy Research (Canberra : Centre for Aboriginal Economic Policy Research, 1996)
Compares labour market outcomes at a sample of CDEP and non-CDEP communities in the Northern Territory; results of policy significance.
Bibliography: p. 14-16.
Keywords: Community Development Employment Projects (Australia); Aboriginal Australians -- Economic conditions; Aboriginal Australians -- Employment -- Northern Territory; Employment subsidies -- Northern Territory; Unemployment -- Northern Territory -- Regional disparities; Employment - Programs - Community Development Employment Projects (CDEP); Social welfare - Government - Social security payments; Community development - Grants and finance; Economics - Economic development; Northern Territory (NT)